Analysing communicative anxiety in French among French language students at the Faculty of Modern Languages and Communication, Universiti Putra Malaysia - Wan Mokhtar, Wan Ikhlas; Ismail, Ahmad Amin (Penerbit UiTM, 2024)
Despite much research focusing on communicative anxiety in foreign languages, few studies have attempted to explore communicative anxiety in French, especially among French language students at the Faculty of Modern Languages and Communication Universiti Putra Malaysia (UPM). In response to this gap, this study explores the communicative anxiety in the French language in a context where exposure to French is limited and illustrates the strategies of French language students in FBMK to reduce communicative anxiety in French. 30 undergraduate students who are studying French Language at FBMK were subjected to a background questionnaire and a questionnaire to measure communicative anxiety. Varimax rotated factor analysis projected students’ anxiety scale through mean score accordingly with test anxiety coming as the highest total mean of 3.31. The findings also show that 26.7% of the participants avoid eye contact with the interlocutor to cope with communicative anxiety. The finding confirms the relationship between anxiety and year of study and provides students with strategies to cope with communicative anxiety.